2012
DOI: 10.1093/mp/ssr120
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Individual Amino Acid Residues to the Endogenous CLV3 Function in Shoot Apical Meristem Maintenance in Arabidopsis

Abstract: As a peptide hormone, CLV3 restricts the stem cell number in shoot apical meristem (SAM) by interacting with CLV1/CLV2/CRN/RPK2 receptor complexes. To elucidate how the function of the CLV3 peptide in SAM maintenance is established at the amino acid (AA) level, alanine substitutions were performed by introducing point mutations to individual residues in the peptide-coding region of CLV3 and its flanking sequences. Constructs carrying such substitutions, expressed under the control of CLV3 regulatory elements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 48 publications
2
60
2
2
Order By: Relevance
“…The full-length 3,932-bp CLV3 genomic sequence including a 1,857-bp 59-upstream sequence, a 559-bp coding region, and a 1,516-bp 39-downstream sequence was amplified (named CLV3F) and cloned as previously described (Song et al, 2012). Using CLV3F as the template, 12 constructs (named CLV3 Ala1-12 ) were made via PCR-based site-directed mutagenesis to replace each of the 12 residues with Ala, one at a time, in the core CLE motif of CLV3 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The full-length 3,932-bp CLV3 genomic sequence including a 1,857-bp 59-upstream sequence, a 559-bp coding region, and a 1,516-bp 39-downstream sequence was amplified (named CLV3F) and cloned as previously described (Song et al, 2012). Using CLV3F as the template, 12 constructs (named CLV3 Ala1-12 ) were made via PCR-based site-directed mutagenesis to replace each of the 12 residues with Ala, one at a time, in the core CLE motif of CLV3 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using CLV3F as the template, 12 constructs (named CLV3 Ala1-12 ) were made via PCR-based site-directed mutagenesis to replace each of the 12 residues with Ala, one at a time, in the core CLE motif of CLV3 ( Fig. 1A; Song et al, 2012), and transformed into wild-type Arabidopsis (ecotype Landsberg erecta [Ler]) to obtain at least 30 independent transgenic plants for each construct. We screened these transgenic plants for the multicarpel clv3 mutant-like phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because positively charged amino-terminal Arg and carboxy-terminal His -His residues are essential for synthetic 12-aa MCLV3p activity (Kondo et al 2006(Kondo et al , 2008Betsuyaku et al 2011;Lee et al 2011) and for transgenic CLV3 complementation in clv3 (Song et al 2012), we hypothesized that CLV3p-FLS2 interactions may be pH dependent. Interestingly, CLV3p activity mediated through FLS2 was abolished at pH 7.6 and was most active at pH 5-6, reflecting the physiological apoplastic environment after protein secretion, whereas flg22 activated similar responses from pH 5 to 7.6 and peaked at pH 7.…”
Section: Differential Peptide-receptor Signalingmentioning
confidence: 99%
“…Molecular genetic and biochemical advances during past decades have revealed that peptides secreted and processed from and around stem cells have pivotal roles in controlling cell identity and developmental processes through multiple receptor kinase complexes in the SAM ( Fig. 1) (Kondo et al 2006;DeYoung and Clark 2008;Jun et al 2008;De Smet et al 2009;Guo et al 2010;Kinoshita et al 2010;Gish and Clark 2011;Matsubayashi 2011;Aichinger et al 2012;Perales and Reddy 2012;Song et al 2012). However, little is known about the dynamic biochemical, molecular, and cellular events and regulatory components constituting the primary signaling processes after peptide ligand perception by receptor kinases in the SAM (Betsuyaku et al 2011;Perales and Reddy 2012).…”
mentioning
confidence: 99%